Maprotiline treatment differentially influences cardiac β-adrenoreceptors expression under normal and stress conditions - Natasa Spasojevic; Predrag Jovanovic; Sladjana Dronjak (Universidade de São Paulo, 2012)
Alterations in cardiac function were observed in antidepressants treated patients and published in several clinical reports. These detected changes could be either a consequence of the treatment or of depression itself, which has already been proved to be a risk factor in heart diseases. In order to determine a possible influence of chronic treatment with norepinephrinergic reuptake inhibitor, maprotiline, on the heart, we investigated gene expression of cardiac β-adrenoceptors both in controls and in animals with signs of depression. The rats were divided into two groups, unstressed controls and those exposed to chronic unpredictable mild stress (CUMS). The groups were further divided into two subgroups, one receiving daily intraperitoneal injections of vehicle (sterile water) and another one maprotiline (10 mg/kg) for four weeks. Tissue samples were collected after the last application. Gene expression of cardiac β1- and β2-adrenoceptor was determined using Real-time RT-PCR analysis. Our results show that in control animals expression of both adrenoreceptors was decreased in the right atria after 4 weeks of maprotiline application. Contrary, the same treatment led to a significant increase in expression of cardiac β1-adrenoceptor in the stressed rats, with no change in the characteristics of β2-adrenoceptor. Our findings might reflect the that molecular mechanisms are underlying factors involved in the development of cardiovascular diseases linked with antidepressant treatment.